2019
DOI: 10.21203/rs.2.14359/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress ulcer prophylaxis with proton pump inhibitors or histamine 2 receptor antagonists in critically ill adults - A meta-analysis of randomized controlled trials with trial sequential analysis.

Abstract: Background Proton pump inhibitors (PPI) and histamine 2 receptor antagonists (H2RA) have been widely used as stress ulcer prophylaxis (SUP) in critically ill patients, however, its efficacy and safety remain unclear. This study aimed to assess the effect of SUP on clinical outcomes in critically ill adults.Methods Literature search was conducted in PubMed, EMBASE, Web of Science, and the Cochrane database of clinical trials for randomized controlled trials (RCTs) that investigated SUP, with PPI or H2RA, vers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In patients with lower risk of CIB, there are no clear guidelines for use. H2RAs may also be preferred due to their lower cost, potential lower risk of pneumonia compared to proton pump inhibitors [14][15][16][17][18]. Furthermore, research has demonstrated that although CIB is decreased with PPIs compared to H2RAs, mortality has not been significantly different between groups, with mortality generally being lower with H2RA use [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with lower risk of CIB, there are no clear guidelines for use. H2RAs may also be preferred due to their lower cost, potential lower risk of pneumonia compared to proton pump inhibitors [14][15][16][17][18]. Furthermore, research has demonstrated that although CIB is decreased with PPIs compared to H2RAs, mortality has not been significantly different between groups, with mortality generally being lower with H2RA use [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding associated with stress ulcers is a problem among critically ill patients such as those with sepsis. Recent improvements in the quality of management for these patients have decreased the incidence of upper gastrointestinal bleeding to 2‐5% 980 . However, preventing stress ulcers is important because the onset of upper gastrointestinal bleeding was correlated with an increased mortality rate 981 .…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%